The Analysis of Parenting Patterns in Instilling Morals of Early Childhood - Yoesoep Edhie Rachmad; Bredyna Agnesiana; Ellyzabeth Sukmawati; Akhmad Ramli; Rony Sandra Yofa Zebua (Program Studi Pendidikan Islam Anak Usia Dini, Institut Agama Islam Ma'arif (IAIMNU) Metro Lampung, 2023)
This study aims to determine the parenting style of parents in instilling morals in children from an early age. The research method used is a qualitative and descriptive analysis approach. Observation, interviews, and questionnaires were used to collect data. And data analysis techniques such as data reduction, presentation, and conclusion drawing. The results found indicate that there is a diversity of parenting styles carried out by student parents in instilling morals in children from an early age; among these parenting styles are democratic, permissive, and authoritarian parenting styles. The democratic parenting pattern shows the greatest level of acceptance compared to the permissive and authoritarian types. So, it can be concluded that, based on the existing research data, parents have a tendency to instill morals at an early age by using democratic parenting.